Inovasi Seni Tatah Timbul Kulit Sapi Pada Produk Fungsional di UMKM Geoge Leather Yogyakarta - Priyono, Rohmad Eko; Novilasari, Ima; Rahmawati, Junende (Corak, 2025)
This research aims to raise the embossed inlay technique applied to functional products made by Geoge Leather Yogyakarta MSMEs. The embossed inlayment technique produced by Geoge Leather Yogyakarta MSME products is one of the innovative products that is the hallmark of the Geoge Leather Yogyakarta Brand DNA. Embossed inlaid products as one of the leather craft arts prioritize hand skills (handicraft) by paying attention to aesthetic and functional values. Through qualitative research with artistic research methods that discuss practice-based research that produces knowledge and technical understanding of embossed inlays applied to plant-based tanned leather media that has not been widely applied to leather industry products that produce bags, shoes, jackets, etc. The identity of Geoge Leather products is not only in terms of technical creation, but also motif designs that raise the local wisdom of the archipelago's culture such as puppets, batik, dance visuals, and so on as part of product innovation that becomes the identity or Brand DNA of the UMKM.ABSTRAKPenelitian ini bertujuan mengangkat teknik tatah timbul yang diterapkan pada produk fungsional karya UMKM Geoge Leather Yogyakarta. Teknik tatah timbul hasil produk UMKM Geoge Leather Yogyakarta sebagai salah satu produk inovasi yang menjadi ciri khas dari Brand DNA Geoge Leather Yogyakarta. Produk-produk tatah timbul sebagai salah satu karya seni kriya kulit mengutamakan keterampilan tangan (handicraft) dengan memperhatikan nilai estetika dan fungsionalitas. Melalui penelitian kualitataif dengan metode penelitian artistic yang membahas tentang penelitian berbasis praktik yang menghasilkan pengetahuan dan pemahaman teknis tatah timbul diterapkan pada media kulit samak nabati yang belum banyak diterapkan pada produk industry kulit penghasil tas, sepatu, jaket, dsb. Identitas produk Geoge Leather tidak hanya dari segi teknis penciptaannya, namun juga desain motif yang mengangkat kearifan lokal budaya Nusantara seperti wayang, batik, visual tarian, dan lain sebagainya sebagai bagian dari inovasi produk yang menjadi identitas atau Brand DNA UMKM tersebut.